2021
DOI: 10.1021/acs.inorgchem.1c00809
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridyl-Decorated Nitronyl Nitroxide–DyIII Single-Molecule Magnet with a Record Energy Barrier of 146 K

Abstract: A nitronyl nitroxide biradical with a capping N-donor group was discovered to improve single-molecule-magnet behavior of the Dy-biradical cluster, generating a magnetic reversal barrier of 146 K. As far as we know, the effective energy barrier of the Dy compound is largest in the nitronyl nitroxide 4f system by far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…13,14 Besides, with a dipyridyl-decorated NIT biradical ligand, a Dy 4 complex with a high energy barrier of 146 K has been reported. 16 These results clearly show that biradical ligands with two NIT units are promising for the construction of interesting Ln-SMMs.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…13,14 Besides, with a dipyridyl-decorated NIT biradical ligand, a Dy 4 complex with a high energy barrier of 146 K has been reported. 16 These results clearly show that biradical ligands with two NIT units are promising for the construction of interesting Ln-SMMs.…”
Section: Introductionmentioning
confidence: 75%
“…These biradicals are mainly based on 1,3-benzene or 1,4-benzene motifs. 12–16 To continue our work for more lanthanide-biradical complexes, we connected the 2-imidazole substituted NIT ligand with two alkyl chains of different lengths and flexibilities. Two bis-bidentate biradical ligands BNITIm-C2 and BNITIm-C4 have been prepared and a series of lanthanide complexes based on these ligands have been synthesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it easy to build heterospin systems in which direct magnetic interactions operate between the metal and radical spin carriers. This has provided many magnetic systems [ 28 ] among which molecular magnets [ 29 , 30 , 31 ], single-molecule magnets [ 31 , 32 , 33 , 34 , 35 , 36 ], or single-chain magnets [ 37 , 38 , 39 , 40 , 41 ]. However, that is not all.…”
Section: Introductionmentioning
confidence: 99%
“…As a class of attractive molecular-based magnetic materials, single-molecule magnets (SMMs) have potential applications in many fields such as ultrahigh-density data storage, quantum computing, and molecular spintronics. Molecular-based magnetic materials constructed from lanthanide metal centers have attracted much attention due to their large magnetic moments and significant magnetic anisotropy caused by strong spin–orbit coupling. Since the first case of the lanthanide single-molecule magnet [Ln­(Pc) 2 ]­(Bu 4 N) (Ln = Tb or Dy; Pc = phthalocyanine) was designed and synthesized in 2003, there has been rapid development of lanthanide SMMs. In particular, dysprosium-based SMMs have made remarkable progress, mainly because Dy­(III) possesses Ising-type magnetic anisotropy originating from the Kramer double ground state, which is an ideal composition for the construction of SMMs. , In the past two decades, mononuclear Dy­(III)-based SMMs have been a research hotspot in the field of molecular magnetic materials. For single-nuclear Dy­(III)-based SMMs, numerous studies have shown that the structure with high symmetry geometry and strong axial crystal field is more likely to generate a large magnetic reversal barrier and a high hysteresis temperature. , However, directional assembly to obtain mononuclear Dy­(III) complexes with high symmetry and specific configuration usually needs to be carried out in an anhydrous and oxygen-free vacuum or nitrogen environment, and the reaction conditions are relatively harsh. ,, …”
mentioning
confidence: 99%